2020
DOI: 10.1155/2020/7649080
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Adenosine A2A Receptor Protects Photoreceptors after Retinal Detachment by Inhibiting Inflammation and Oxidative Stress

Abstract: Purpose. Adenosine A2A receptor (A2AR) signaling is neuroprotective in some retinal damage models, but its role in neuronal survival during retinal detachment (RD) is unclear. We tested the hypothesis that A2AR antagonist ZM241385 would prevent photoreceptor apoptosis by inhibiting retinal inflammation and oxidative stress after RD. Methods. The A2AR antagonist ZM241… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Another type of adenosine receptor, Adenosine A 2A receptor (A 2A R), is also expressed by the MG. The inhibition of A 2A R decreases GFAP upregulation and IL-1β expression of MG, and suppresses ROS overproduction, resulting in attenuation of photoreceptor apoptosis after RD ( Gao et al, 2020 ).…”
Section: Mg Metabolism and The Relationship With Retinal Inflammationmentioning
confidence: 99%
“…Another type of adenosine receptor, Adenosine A 2A receptor (A 2A R), is also expressed by the MG. The inhibition of A 2A R decreases GFAP upregulation and IL-1β expression of MG, and suppresses ROS overproduction, resulting in attenuation of photoreceptor apoptosis after RD ( Gao et al, 2020 ).…”
Section: Mg Metabolism and The Relationship With Retinal Inflammationmentioning
confidence: 99%
“…Indeed, previous research has indicated that A2AR is strongly associated with OS. The A2AR antagonist ZM241385 was an effective suppressor of microglial proliferation and reactivity, OS and photoreceptor apoptosis in a mouse model of retinal detachment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion made by others [ 7 ] of using antioxidants to improve better visual recovery choices after RRD are of interest. Gao et al [ 35 ] demonstrated that blocking oxidative stress in experimental retinal detachment improved the apoptosis of photoreceptors. This may be an interesting future avenue of research to attempt to prevent the apoptosis of photoreceptors and, therefore, to improve the vision of patients with retinal detachment.…”
Section: Discussionmentioning
confidence: 99%